Critical current survival in the YBCO superconducting layer of a delaminated coated conductor. (26th February 2018) - Feng, Feng; Fu, Qishu; Qu, Timing; Mu, Hui; Gu, Chen; Yue, Yubin; Wang, Linli; Yang, Zhirong; Han, Zhenghe; Feng, Pingfa
Abstract: A high-temperature superconducting coated conductor can be practically applied in electric equipment due to its favorable mechanical properties and critical current ( I c ) performance. However, the coated conductor can easily delaminate because of its poor stress tolerance along the thickness direction. It would be interesting to investigate whether the I c of the delaminated YBa2 Cu3 O7− δ (YBCO) layer can be preserved. In this study, coated conductor samples manufactured through the metal organic deposition route were delaminated by liquid nitrogen immersion. Delaminated samples, including the YBCO layer and silver stabilizer, were obtained. Delamination occurred inside the YBCO layer and near the YBCO–CeO2 interface, as suggested by the results of scanning electron microscopy (SEM) and x-ray diffraction. A scanning Hall probe system was employed to measure the I c distribution of the original sample and the delaminated sample. It was found that approximately 50% of the I c can be preserved after delamination, which was verified by I c measurements using the four-probe method. Dense and crack-free morphologies of the delaminated surfaces were observed by SEM, which accounts for the I c survival of the delaminated YBCO layer. The potential application of the delaminated sample in superconducting joints was discussed based on the oxygen diffusion estimation.